ANALISIS MAKNA KONOTATIF LIRIK LAGU DALAM ALBUM “BEST SELECTION BLANC” OLEH AIMER - Essy Cahyani; Hendri Zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2021)
AbstrakThis research is motivated by the difficulty of understanding the connotative meaning contained in a sentence so that it can lead to misunderstandings in interpreting the meaning that the speaker wants to convey. The objectives of this study were to: (1) describe the connotative meanings contained in the song lyrics in album Best Selection “Blanc” by Aimer, (2) describe the types of connotative meanings used in the song lyrics in the album Best Selection "Blanc" by Aimer. This type of research is qualitative research using descriptive methods. The data in this study are words, phrases, and sentences that contain connotative meanings. While the source of the data taken in this study is the song lyrics in the album Best Selection "Blanc" by Aimer which consists of 5 songs, namely Kataomoi, Polaris, Akane Sasu,  Kimi O Matsu, and Re: Pray. The result of this research is the discovery of 12 song lyrics that contain connotative meanings. Of the 12 data, there are 6 pieces of data that are included in the positive connotative meaning and 6 pieces of data that are included in the negative connotative meaning. So it can be concluded that the types of connotative meanings used in the album Best Selection “Blanc” use both types of classifications of connotative meanings according to Hook's theory, namely positive connotative meanings and negative connotative meanings. Then on the album Best Selection "Blanc" this type of connotative meaning that is widely used is negative connotative meaning. Abstrak  Penelitian ini dilatarbelakangi oleh sulitnya memahami makna konotatif yang terkandung dalam sebuah kalimat sehingga dapat menimbulkan kesalahpahaman dalam mengartikan maksud yang ingin disampaikan oleh penuturnya. Tujuan dari penelitian ini adalah untuk: (1) mendeskripsikan makna konotatif yang terkandung pada lirik lagu dalam album Best Selection “Blanc” oleh Aimer, (2) mendeskripsikan jenis-jenis makna konotatif yang digunakan pada lirik lagu dalam album Best Selection “Blanc” oleh Aimer. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan metode deskriptif. Data dalam penelitian ini adalah kata, frasa, serta kalimat yang mengandung makna konotatif. Sedangkan sumber data yang diambil dalam penelitian ini adalah lirik lagu dalam album Best Selection “Blanc” oleh Aimer yang terdiri dari 5 lagu yaitu Kataomoi, Polaris, Akane Sasu,  Kimi O Matsu, dan  Re:Pray. Hasil dari penelitian ini adalah ditemukannya 10 lirik lagu yang mengandung makna konotatif. Dari 10 data tersebut terdapat 4 buah data yang termasuk dalam makna konotatif positif dan 6 buah data yang termasuk dalam makna konotatif negatif. Sehingga dapat dismpulkan bahwa jenis-jenis makna konotatif yang digunakan dalam album Best Selection “Blanc” ini menggunakan kedua jenis pengklasifikasian makna konotatif menurut teori Hook yaitu makna konotatif positif dan makna konotatif negatif. Kemudian pada album Best Selection “Blanc” ini jenis makna konotatif yang banyak digunakan adalah makna konotatif negatif.